Russian economic reform - Jim Leitzel (Routledge, 1995)
Transitions from socialism to capitalism are complex, both in theory and practice. Russian Economic Reform enables the reader to come to a much better understanding of these momentous changes, by providing a clear and accessible account of the major features of transition. It argues that attempts to portray the reform process is a disaster are misconceived, because they fail to take account of just how badly the pre-reform economy was doing. Many of the problems that are emerging now have their antecedents in the earlier economic system.
Keywords: 300; Systemtransformation; Russland